PEMILIHAN JENIS PENANGKAL PETIR UNTUK MENGAMANKAN AREA GEDUNG BESERTA PERALATAN PADA PERUMAHAN NUSA DUA HIGHLAND - Kharis Biantoro; I Wayan Arta Wijaya; I Gusti Ngurah Janardana (Jurnal SPEKTRUM, 2020)
The selection of lightning rods in the Nusa Dua Highland housing estate aims to securethe housing area from lightning strikes, because the housing has not been protected by lightningrods and earthing system components which are very difficult because they have rocky soil types.The average number of lightning strikes per year with a density value of 31 per km2 and populationdensity, land use for houses and buildings have a very high level of vulnerability, so lightning rodsare needed to secure the Nusa Dua Highland residential area. Lightning rods to be used areconventional lightning rods or Evo Franklin (E.F). The selection of the type of lightning rod is done byanalyzing technical and economical. The results achieved in this study are the type of lightning rodsuitable for housing Nusa Dua Highland is the E.F lightning rod with an earthing system. Becausefrom technical analysis, 1 E.F lightning rod is able to protect the entire residential area with 37,994m2 of protection area from the 22,444 m2 housing area, while 1 conventional lightning rod is onlyable to protect 1 house from a total of 147 housing units. In terms of economical cost of installing E.Flightning rods is much cheaper at a cost of Rp. 104,450,000. Conventional lightning rods cost Rp.14,390,000 for 1 housing unit and to protect the entire housing using conventional lightning rodsneeded 147 lightning rods at a cost of Rp. 2,115,390,000.